'Determination is negation': The Adventures of a Doctrine from Spinoza to Hegel to the British Idealists. Issue 1 (4th April 2016) - Stern, Robert
Abstract: This article is a discussion of Hegel's conception of the principle 'omnis determinatio est negatio', which he attributes to Spinoza. It is argued, however, that Spinoza understood this principle in a very different way from Hegel, which then sets up an interpretative puzzle: if this is so, why did he credit Spinoza with formulating it? This puzzle is resolved by paying attention to the context in which those attributions are made, while it is also shown that the British Idealists (unlike many contemporary commentators) were aware of the complexities in the Spinoza–Hegel relation on this issue. The paper also addresses some of the philosophical debates raised by this question, and the light it sheds on Hegel's critique of Spinoza as a monist.